Ціна мовної уніфікації: відновлення івриту - Спольський, Б. (Народна творчість та етнографія, 2008)
The revitalisation and revemacularization of the Hebrew language depended on a unique set of circumstances. In this paper, I ask what was unique about the situation of Hebrew so that it was successfully revitalized and re-vernacularised. Secondly, I ask what was the cost of this success, in addition to specific conditions, the success of revival depended on a broad ideological consensus regarding the use of Hebrew in Erefz Israel. One regrettable effect of this was the squandering of the rich and diverse multilingual heritage that had previously marked the Jewish people, who over the centuries had maintained alongside Hebrew and-Aramaic for sacred functions and literacy an internal community language like Yiddish, Ladino, or Judeo-Arabic, mastery of one or more co-territorial vernaculars.